Absence of H-2 antigens capable of reacting with cytotoxic T cells on a teratoma line expressing a T/t locus antigen. - Forman, J (1975)
An established cell line of murine teratoma cells (F9), which lacks serologically detectable H-2 that is determined by a wild-type T/t locus gene. These cells are not killed and do not react with cytotoxic T cells sensitized to H-2 antigens in a cell-mediated lympholysis assay. Modification of spleen cells from the strain or origin (129) of this teratoma line with trinitrobenzene sulfonic acid allows the generation of syngeneic killer cells that display a cytotoxic effect against trinitrophenyl-modified splenic targets, but not against trinitrophenyl-modified F9 targets. Thus, the F9 antigen is structurally similar to H-2b but does not act as a target antigen in the cell-mediated lympholysis assay for anti-H-2b cytotoxic T cells, nor does it crossreact with H-2b antigens at the T cell level.